Upaya Peningkatan Motivasi Kewirausahaan Pemuda Desa Kayen Melalui Pelatihan Produk Olahan Ubi Kayu - Miftachul Chusnah; Yessita Puspaningrum; Mochammad Chumaidi; Nur Ismianah (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2021)
Cassava is a carbohydrate-producing commodity that is commonly found in rural areas. Simple processing of cassava makes this commodity rarely in demand by adolescents and children. Efforts to diversify products need to be done, one of which is through training in SEUKAPE processing. The target audience for this community service activity is village youth in the Kayen Village area, Bandarkbuildingmulyo District, Jombang Regency. This activity was carried out at the Kayen Village Hall which is located in the Kayen Village Head Office in October 2020 with a total of 20 participants. The series of community service activities including entrepreneurship workshops, training on making SEUKAPE and product displays were well attended by the participants. The results of the activity showed that the participants were enthusiastic in making SEUKAPE as an example of local processed products that can become the hallmark of Kayen Village.